Yield and cost-effectiveness of laboratory testing to identify metabolic contributors to falls and fractures in older persons. Issue 1 (December 2015) - Johnson, Kate; Suriyaarachchi, Pushpa; Kakkat, Mohammed; Boersma, Derek; Gunawardene, Piumali; Demontiero, Oddom; Tannenbaum, Cara; Duque, Gustavo
Abstract Summary Falls and fractures constitute a major cause of morbidity and mortality among older adults. Although falls and fractures share similar risk factors, there is no integrated approach to identifying secondary causes of both entities. We report a cost-effective approach to identify metabolic causes of falls and fractures in the clinical setting. Purpose Falls and fractures are a major cause of morbidity and mortality among older adults. Metabolic disorders contributing to the combined risk of falls and fractures are frequent but often go undetected. The most efficient and cost-effective laboratory screening strategy to unmask these disorders remains unknown. The purpose of this study was to identify the most cost-effective laboratory tests to detect undiagnosed metabolic contributors and to decide treatment of these disorders in older persons. Methods This is a cross-sectional study design, which included all participants attending the Falls & Fractures Clinic, Nepean Hospital (Penrith, Australia) between 2008 and 2013. Chemistry profile included 25(OH) vitamin D, parathyroid hormone (PTH), albumin, creatinine, calcium, phosphate, vitamin B-12, folate, and thyroid-stimulating hormone (TSH) for all patients, and serum testosterone in men. The number of new diagnoses identified and their cost-effectiveness (cost in US per patient screened and cost per new diagnosis) were calculated. Results A total of 739 participants (mean age 79, 71 % female) were assessed. Among 233 participants with complete laboratory tests, previously undiagnosed disorders were identified in 148 (63.5 %). Vitamin D deficiency (27 %) and hyperparathyroidism (21.5 %) were the most frequent diagnoses. A testing strategy including serum vitamin D, calcium, PTH, creatinine/estimated glomerular filtration rate (eGFR), and TSH for all patients and serum testosterone in men would have been sufficient to identify secondary causes of falls and fractures in 94 % of patients at an estimated cost of 190.19 per patient screened and 257.64 per diagnosis. Conclusions The minimum cost-effective battery for occult metabolic disorders in older adults at risk of falls and fractures should include serum vitamin D, PTH, TSH, creatinine/eGFR, testosterone (in men), and calcium.